Characteristics of wideband dipole phased array of L-band - S. V. Ballandovich; G. A. Kostikov; L. M. Liubina; M. I. Sugak; N. V. Samburov (Известия высших учебных заведений России: Радиоэлектроника, 2015)
Results of designing of broadband equidistant phased antenna array (PAA) of UHF range, built on the basis of dipole emitters are shown. Frequency dependences of the reflection coefficients in the path of the power elements in the infinite PAA, as well as the frequency and dynamic dependencies of the gain for the broadband PAA, consisting of a finite number of elements are presented.